On mapping urban community resilience: Land use vulnerability, coping and adaptive strategies in Ghana - Ibrahim, Abdul-Salam; Kuuire, Vincent; Kepe, Thembela (Journal of environmental management, 2024)
Cities across the globe are prioritizing resilience in the wake of increasing climate change-related disasters. About 44% of these disasters are floods and their manifestation in cities is more pronounced, threatening urban social, ecological, and economic systems. This study draws on community resilience and participatory GIS, to examine land use vulnerability to flooding and local coping and adaptive strategies to achieve resilience. Using Ghana as a case study, the results show that participatory mapping offers community resilience benefits by providing context to community resilience challenges and potentials, enabling a deeper understanding of socio-environmental coupling that contributes to flood vulnerability and builds on community adaptive strategies through harnessing local community knowledge. We identified that topography, poor drainage and road network, rainfall variability, residents’ land use practices, and land use planning conundrum drive disparities in land use vulnerability to flooding. Participants underscored the necessity of critical urban infrastructure in facilitating community adaptability to floods. The findings indicate that socio-spatial inequities threaten urban community resilience, especially in increasingly cosmopolitan urban contexts, by putting the marginalized urban population in a more vulnerable position. We recommend the prioritization of recognitional equity in community resilience planning efforts to allow for the targeting of resilient interventions that reflect and respect social differentiation in the urban environment so that outcomes will not exacerbate or generate new urban socio-spatial inequalities. •Flood victims use participatory GIS to map vulnerability, coping and adaptive strategies.•Participatory mapping provides context to community resilience challenges and potentials.•Anthropogenic and natural elements drive land use vulnerability to flooding.•Urban inequalities put marginalized urban populations in a more vulnerable position.•Recognitional equity should be prioritized in community resilience planning.